+0  
 
0
4
1
avatar+1479 

Let $a$ and $b$ be the roots of $x^2 + 7x - 4 = -x^2 + 9x + 6$. Find $(a + 3) + (b + 3).$

 Dec 23, 2023
 #1
avatar+16 
+1

x2 + x2 + 7x - 9x - 4 - 6 = 0

2x2 - 2x - 10 = 0

 

Divide both sides by 2:

x2 - x - 5 = 0

 

Now, find the roots using the quadratic formula:

x = 1 +/- √1 - 4(1)(-5)                   1 +/-   √21

      ------------------------         =     -----------------

                  2                                       2

 

So, a = (1 + √21) / 2,  b = (1 - √21) / 2

 

We are trying to find what is (a + 3) + (b + 3), so we just plug in the numbers:

     1 + √21                 1 - √21                    1      √21         1       √21

(   ----------- +  3) + (   ---------- + 3) = 3 --  +  -----  +  3 ---  -  -----  = 3.5 + 3.5 = 7

         2                           2                         2        2           2         2

 Dec 23, 2023

3 Online Users

avatar